Impact of Conservation Agricultural Practices on Economics of Wheat Cultivation in Haryana - Yogi, Vikram; Kar, Amit; Kumar, Pramod (International Journal of Bio-resource and Stress Management, 2016)
Conservation agriculture can be seen as a new way forward for conserving resources and enhancing the productivity to achieve the goal of sustainable agriculture. The current study was undertaken in wheat to examine the economic feasibility of conservation agriculture practice comparison with conventional agricultural practices in the wheat growing district of Karnal and Kurkshetra in Haryana state. The sample size of 120 farmers was taken from the four villages. Cost estimation was done to examine the economic feasibility of conservation agriculture. Garrett’s ranking was used to find out the factors responsible for adoption of conservation agriculture. The cost of cultivation in the zero seed drill farms (Rs. 33, 232 ha-1) was lower than the cost incurred by the conventional farms (Rs. 37, 211 ha-1) and the Rotavator farms (Rs. 36, 838 ha-1). This was due to lower cost incurred towards human labour, machine labour, seed and irrigation in zero seed drill farms. The benefit costratio under zero tillage was 2.02 and under rotavator and conventional method were 1.80 and 1.73. This shows that zero tillage is economically feasible. The result showed that the reasons for practicing conservation technology were reduction in cost and higher income. The respondents in the main reasons for not adopting the conservation technology is ‘availability rotvator, the high cost of machine like turbo seeder, non availability of zero seed drill; extension benefits limited to large and progressive farmers are the constraints for non adoption of conservation practices.